BIBLICAL FESTIVALS AND HINDU FEASTS - Nereparampil, Lucius (1990)
Feasts and celebrations keep the human spirit happy and elevated from the material level of man's existence and brings him somehow to the divine sphere. It is such celebrations that break the monotony of human life and give man a foretaste of heavenly bliss. They help man to acknowledge the break-through of a transcendent God in his history. and thereby to come in closer contact with that benevolent God.
Keywords: BIBLICAL FESTIVALS; Celebration of the Passover; Feast of Liberation: The Passover; Feast of Purim; Feast of Tents; Feast of Weeks or the Pentecost; Feast of the Unleavened Bread; Festival of Atonement; Festival of the Hanukkah or Dedication; Festivals of Harvest; Lunar Calendar; Nature of this Feast; Passover in the New Testament; Passover in the Old Testament; Ritual of the Passover; Ritual of the Passover Meal; Ritual of this Feast